Strong but heterogeneous distributional responses to climate change are projected for temperate and semi‐arid stream vertebrates. Issue 8 (16th March 2022) - Elliott, Jennifer; Passy, Sophia I.; Pound, Katrina L.; Merritt, Glenn; Polkowske, Stacy; Larson, Chad A.
Abstract: Globally, freshwater systems are threatened by climate change, so projections under various climate change scenarios are needed to inform efforts to protect and conserve already vulnerable taxa. Here, the change in distribution of stream vertebrates was investigated under different greenhouse gas emission scenarios. Using occurrence data from multiple stream surveys in Washington State spanning 559 sites and 24 years, species distribution models for 23 aquatic vertebrate taxa (21 fish and two amphibians) were developed. Models projected changes in taxon distributions for 2070 under representative concentration pathways (RCPs) ranging from 2.6 to 8.5 W m −2 . To assess potential biological impacts of these predictions, changes in taxon richness and beta diversity of stream vertebrates were also investigated. Moreover, predictor variables were examined to assess which ones were more important in determining taxon distributions. Substantial changes in the spatial distribution of stream vertebrates were projected for all RCP scenarios by 2070, but the greatest changes were expected to occur under RCP 6.0 and 8.5. The taxa evaluated were predicted to experience substantial increase, decrease, or shift in distribution. Taxon richness of stream vertebrates was forecasted to increase with RCP scenario relative to historical conditions, suggesting that distributional expansions outpaced distributional contractions. However, beta diversity was predicted to decrease considerably, suggesting increased biotic homogenization. Variables important for determining future distributions varied by taxa, with most species influenced by a combination of variables. These results indicate that failing to reduce greenhouse gas emissions will lead to dramatic impacts on stream vertebrates. The magnitude of predicted future impacts was dependent upon RCP scenario, so advancements in policy to reduce carbon emissions are necessary. We also recommend as potential conservation measures preserving cold‐water refugia and increasing efforts to lower stream water temperatures by, for example, expanding the riparian cover and/or linking surface water to groundwater.